Nucleolin recognizing silica nanoparticles inhibit cell proliferation by activating the Bax/Bcl-2/caspase-3 signalling pathway to induce apoptosis in liver cancer - Xiang, Liangliang; Li, Yun; Gu, Xinyu; Li, Shujie; Li, Junwei; Li, Jinlong; Yi, Yongxiang (Frontiers in Pharmacology, 2023)
Multifunctional nanocarrier platforms have shown great potential for the diagnosis and treatment of liver cancer. Here, a novel nucleolin-responsive nanoparticle platform was constructed for the concurrent detection of nucleolin and treatment of liver cancer. The incorporation of AS1411 aptamer, icaritin (ICT) and FITC into mesoporous silica nanoparticles, labelled as Atp-MSN (ICT@FITC) NPs, was the key to offer functionalities. The specific combination of the target nucleolin and AS1411 aptamer caused AS1411 to separate from mesoporous silica nanoparticles surface, allowing FITC and ICT to be released. Subsequently, nucleolin could be detected by monitoring the fluorescence intensity. In addition, Atp-MSN (ICT@FITC) NPs can not only inhibit cell proliferation but also improve the level of ROS while activating the Bax/Bcl-2/caspase-3 signalling pathway to induce apoptosis in vitro and in vivo. Moreover, our results demonstrated that Atp-MSN (ICT@FITC) NPs had low toxicity and could induce CD3+ T-cell infiltration. As a result, Atp-MSN (ICT@FITC) NPs may provide a reliable and secure platform for the simultaneous identification and treatment of liver cancer.